Governance and Poverty Eradication Policy Performance During the NRM Administration in Uganda 1986 – 2020. - Mucunguzi, Abel; Katabaazi, Anny Bwengye (Kabale University, 2023)
Poverty in Uganda is attributed to diseases, limited access to land, large families, lack of markets for agricultural produce, lack of credit facilities, lack of education and vocational training, lack of jobs, high unfair taxes and market dues, death of family bread winners, ignorance and lack of information, idleness and laziness, insurgency and gender inequalities among others. This is the identifiable poverty structural complex within which any actor on poverty reduction and eradication has to work. However, despite the above elaborate classification of the causes of poverty in Uganda and the enactment of numerous anti-poverty policies, less effort has been expended in analyzing why the poverty situation in Uganda has not significantly changed since the NRM administration. This study therefore attempted inter alia to fill this research gap and also sought to introduce new concepts that can improve poverty reduction and eradication agenda in Uganda. The idea behind this research is that if the causes of the slow progress in poverty reduction are not identified and targeted holistically through policy and inculcation of good governance at all levels of government administration, it will be difficult for Uganda to achieve significant poverty reduction and eradication in the long run. Consequently therefore, the main objective of the study was to establish whether or not a relationship exists between governance and anti-poverty policy performance in Uganda and to generate governance practices that can be applied for better anti-poverty policy performance in Uganda in the future. Following on this objective it is hypothesized that a possible relationship exists between governance practices at all levels of government administration and poverty reduction so much so that particular governance practices are crucial in poverty reduction. A mixed research methodology was adopted in the study and a number of questions were adopted to assist in probing this hypothesis.